(untitled) (Multidisciplinary Journal of Science and Technology, 2025)
This article analyzes the place of Samarkand in the history of the Bukhara Emirate, as well as its crafts, internal and external trade relations, based on historical sources. As one of the cities that made a significant contribution to world civilization, the development of urban crafts during the reign of the Mangid dynasty of the Samarkand Bekliy can be seen from the fact that great attention was paid to trade issues and paper production in Samarkand. The fact that their historical monuments have been preserved for centuries has amazed people even in the memoirs of this period. It is emphasized that the tomb of Amir Temur, made of artificial stone, still exists in Samarkand, and that there are even more historical monuments in this city. We can see that in the 18th century, the Samarkand principality of the Bukhara Emirate had a special place in crafts and trade